2017
DOI: 10.1161/circulationaha.116.026318
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a Drone Network to Deliver Automated External Defibrillators

Abstract: Background Public access defibrillation programs can improve survival after out-of-hospital cardiac arrest (OHCA), but automated external defibrillators (AEDs) are rarely available for bystander use at the scene. Drones are an emerging technology that can deliver an AED to the scene of an OHCA for bystander use. We hypothesize that a drone network designed with the aid of a mathematical model combining both optimization and queuing can reduce the time to AED arrival. Methods We applied our model to 53,702 OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(152 citation statements)
references
References 59 publications
(64 reference statements)
1
140
1
10
Order By: Relevance
“…Research about AED-equipped drones is new and has primarily focused on time elements because rapid intervention is critical for patient outcomes [21•]. Drones may be safe and feasible for delivering an AED for out-of-hospital cardiac arrest using Geographic Information System (GIS) tools, which could automatically deploy drones [20•].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research about AED-equipped drones is new and has primarily focused on time elements because rapid intervention is critical for patient outcomes [21•]. Drones may be safe and feasible for delivering an AED for out-of-hospital cardiac arrest using Geographic Information System (GIS) tools, which could automatically deploy drones [20•].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, investigators reported no adverse events nor technical issues during any of the out-of-sight flights. Most recently, another group used geographical and mathematical models to design a drone network in a large area composed of rural and urban regions [21•]. Investigators used a theoretical drone network to quantify the drone network size required to deliver an AED faster than the median 911 times reported for the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, Boutilier et al 26 investigated the possibility of using a drone network to optimize AED delivery to sites of out-of-hospital cardiac arrests efficiently to improve AED utilization ahead of historical 911 response times in Toronto. Using mathematical modeling, their primary analysis quantified the drone network size required to deliver an AED 1, 2, or 3 minutes faster than historical median 911 response times.…”
Section: Resuscitation and Response To Cardiac Arrestmentioning
confidence: 99%
“…63 More recently, the concept of having a drone network designed to deliver AEDs to the site of an out-of-hospital cardiac arrest has been modeled, with results demonstrating that such a strategy could result in the quicker availability of AEDs. 64 Further field testing is required to validate this interesting concept. One caveat, however, is that although having shorter AED response times should logically result in reduced SCD mortality, another study found that the deployment of AEDs in the homes of patients early after anterior MI did not result in reduced mortality compared with training family members in basic life support methods, suggesting that multiple factors influence the use of AEDs in the community.…”
Section: Community Preparednessmentioning
confidence: 99%